Über die Schnittflächen im Produkt der Faserungen - Matuzevičius, A. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матузявичюс. Секущие поверхности произведения расслоенийA. Matuzevičius. Sluoksniavimų sandaugos kertamieji paviršiai